Business Model Redesign for Dine-in Services Using Consumer Values Post COVID-19 - Deshmukh, Arvind; Saxena, Neelam; Sinha, Poonam (AMC Indian Journal of Entrepreneurship, 2022)
The growing working class and rising incomes of Indian urban consumers have significantly increased the consumption of outside food. The Indian restaurant industry was growing substantially before COVID-19 hit the country. The pandemic affected businesses nationwide, and the restaurant industry was no exception. To rebuild their businesses, restaurant owners need to redesign their business models. This paper suggested a customer-centric business modeling view of the restaurant industry. Some fundamental consumer values can anchor restaurants to redesign their business models based on customer preferences. This exploratory study identified consumer values and analyzed their importance from a diner’s perspective.